Effective latent heat thermal energy storage system using thin flexible pouches. (February 2019) - Park, Jinsoo; Shin, Dong Ho; Lee, Seung Joo; Shin, Youhwan; Karng, Sarng Woo
Highlights: A LHTES system was designed and fabricated with stacking flexible PCM pouches. The LHTES system has 1.4 times heat discharging capacity of water storage system. The LHTES system significantly reduced process time compared with the spherical capsule system. Abstract: Thermal energy storage is an essential technology for using renewable energy to reduce building energy consumption. Among the various energy technologies, much attention has been paid to latent thermal energy storage system using phase change materials because of its large capacity of thermal energy. However, due to the low thermal conductivity of the phase change materials, the system has disadvantages at low charging and discharging rates. To address this issue, a new latent heat thermal energy storage system using a flexible and thin pouch is proposed. The effectively designed pouch arrangement and thin pouch shape provide better heat transfer performance. The real product is tested at various flow rates of heat transfer fluids and the thermal and fluid characteristics of the system are analyzed by the computational fluid dynamics model. As a result, the proposed system has 1.4 times larger amount of discharged energy than that of the water storage system. Moreover, the system can reduce charging, discharging, and total process times by 1.7, 2.5, and 2.2 times, respectively, compared with the conventional sphere capsule piling system.